2020
DOI: 10.22190/fupes200226003d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Functional Characteristics of Hand Grip Strength in Young Female Handball Players

Abstract: The aim of this research was to define differences in functional and mechanical characteristics of isometric hand grip (HG) strength between young female handball players and the CG comprised of physically active girls with no experience in sport. 70 individuals participated in the research, 36 of whom were the best young female handball players (of cadet and junior categories) while 34 girls comprised the CG. The results obtained show that the young female handball players who took part in the tests achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For assessment of BF, 32 studies used skinfold measurements [ 5 , 10 , 16 , 17 , 21–48 ], 15 studies used BIA [ 9 , 26 , 49–61 ], 12 studies used DXA [ 20 , 62–72 ] and six studies used densitometry [ 45 , 73–77 ]. Vargas et al [ 45 ] and Buśko & Lipińska [ 26 ] directly compared skinfold measurements to densitometry and BIA, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For assessment of BF, 32 studies used skinfold measurements [ 5 , 10 , 16 , 17 , 21–48 ], 15 studies used BIA [ 9 , 26 , 49–61 ], 12 studies used DXA [ 20 , 62–72 ] and six studies used densitometry [ 45 , 73–77 ]. Vargas et al [ 45 ] and Buśko & Lipińska [ 26 ] directly compared skinfold measurements to densitometry and BIA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that BF has a relatively high inverse association with vertical jump performance (BF alone seems to explained 57% of vertical jump variability, and 66% of variability when combined with sex or body weight) [ 12 ], it is reasonable to expect that elite volleyball players would have lower BF values than their non-elite peers, similar to other team sports such as basketball where body composition has been found to discriminate between levels of competition [ 14 ]. However, while some studies have confirmed this hypothesis [ 5 , 10 , 15 ], others have reported no or unclear differences in BF between playing levels [ 9 , 16 , 17 ]. Additionally, although BF is routinely assessed, volleyball-specific BF recommendations are lacking, making it difficult for researchers and practitioners to interpret measurement results.…”
Section: Introductionmentioning
confidence: 99%
“…U dosadašnjim istraživanjima, polni dimorfizam je uglavnom praćen na nivou maksimalne izometrijske sile. Prosečne vrednosti procentualnih razlika maksimalne sile u pogledu pola, u dostupnoj literaturi, bile su na nivou od oko 30% u korist ispitanika muškog pola (Komi & Karlson, 1978;Hakkinen, 1991;Demura et al, 2003;Dopsaj et al, 2009;Schmitz & Shulz, 2010). U cilјu utvrđivanja razlike maksimalne izometrijske sile mišića opružača nogu u funkciji pola, Komi & Karlsson (1978) su ustanovili da su prosečne vrednosti maksimalne izometrijske sile ekstenzora nogu kod odbojkašica bile na nivou od 80,3% izmerenih prosečnih vrednosti kod odbojkaša.…”
Section: Diskusijaunclassified
“…Takođe je utvrđeno da je ispitanicima muškog pola potrebno manje vremena da postignu isti nivo maksimalne sile, posebno kod njenih viših vrednosti (za postizanje sile od 2000 N odbojkašicama je potrebno 331 ± 19 ms, a odbojkašima 93 ± 24 ms). Da bi se definisao polni dimorfizam maksimalne sile stiska šake, utvrđeni koeficijent je bio na približno istom nivou kao i maksimalna sila u različitim mišićnim grupama, za desnu ruku 0,5922 i za levu 0,5829 (Dopsaj et al, 2009). Važnost procene stope maksimalnog razvoja sile leži u činjenici da je vreme potrebno za dostizanje specifičnog nivoa razvoja sile ponekad veoma značajno u pogledu pola.…”
Section: Diskusijaunclassified
See 1 more Smart Citation